Using Omics Technologies and Systems Biology to Identify Epitope Targets for the Development of Monoclonal Antibodies Against Antibiotic-Resistant Bacteria - Martín-Galiano, Antonio J.; McConnell, Michael J. (Frontiers in Immunology, 2019)
Over the preceding decades, antimicrobial resistance has emerged as an important threat to public health due to the global dissemination of multidrug resistant strains from several bacterial species. This worrisome trend, in addition to the paucity of new antibiotics with novel mechanisms of action in the development pipeline, warrants the development of non-antimicrobial approaches for combating infection caused by these isolates. Monoclonal antibodies (mAbs) have emerged as highly effective molecules for the treatment of multiple diseases. However, in spite of the fact that antibodies play an important role in protective immunity against bacteria, only three mAb therapies have been approved for clinical use in the treatment of bacterial infections. In the present review, we briefly outline the therapeutic potential of mAbs in the treatment of bacterial diseases, and discuss how their development can be facilitated when assisted by “omic” technologies and interpreted under a systems biology paradigm. Specifically, methods employing large genomic, transcriptomic, structural and proteomic datasets allow for the rational identification of epitopes. Ideally, these include those that are present in the majority of circulating isolates, highly conserved at the amino acid level, surface exposed, located on antigens essential for virulence and expressed during critical stages of infection. Therefore, these knowledge-based approaches can contribute to the identification of high value epitopes for the development of effective mAbs against challenging bacterial clones.